O-5 A systematically structured review on biomarkers of dying in cancer patients at the end of life; an exploration of potential mechanisms for the biology of dying. (1st March 2017) - Reid, Victoria; McDonald, Rachael; Nwosu, Amara Callistus; Mason, Stephen R; Probert, Chris; Ellershaw, John E; Coyle, Seamus
Abstract : Background: The Neuberger review made a number recommendation to improve end of life care, including research into the biology of dying. An important aspect of the biology of dying is the identification of biomarkers of the dying process. Biomarkers have the potential to assist clinicians in recognising dying, in particular how to distinguish dying from reversible acute deterioration. Objectives: To critically appraise the existing literature on prognostic biological factors that impact survival in advanced cancer patients in the last days, weeks or months of life; to identify prognostic models for advanced cancer patients, which could assist clinicians to prognosticate in the last days, weeks or months of life; and to identify candidate biomarkers of the dying process that can be measured serially in bodily fluids. Methods: A systematically structured review was conducted using three electronic databases. A hand search of six peer-reviewed journals and conference abstracts was also conducted. Studies reporting biomarkers of dying in cancer patients with a median survival of ≤90 days, and post-mortem studies were included. Results: 30 articles were included. There is grade A evidence for the following biological factors: serum CRP, WBC count, lymphopaenia, serum sodium, urea, ALP and hypoalbuminaemia. An additional nine prognostic factors were identified with grade B evidence including: thrombocytopaenia, elevated vitamin B12, hyperbilirubinaemia, hypocholesterolaemia, elevated AST, ALT, LDH and INR. In the last two weeks of life, a number of biomarkers have been identified but limitations exist. No post-mortem studies met the inclusion criteria. Conclusion: The biology of dying is an important area for future research interest. The evidence base to date is largely focused on symptoms, signs and prognostic factors. We identify a number common themes shared amongst advanced cancer patients, candidate biomarkers of dying, and areas for future research including non-invasive research methodologies.